Social Movements on Rempang Island, Oligarchy and Unjust Power: A Preliminary Study - Sahrasad, Herdi; Al Chaidar; Iskandar Zulkarnain; Ti Aisyah (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2023)
This paper argues that the authoritarianism of the current Joko Widodo government can be seen in this conflict between the state and society in Rempang Island. Residents of Rempang, Batam, numbering in the thousands, have steadfastly refused to leave their homes. In order to advance the Rempang Eco City National Strategic Project (PSN), relocation to Galang Island is being considered. It was inevitable that civilians would rebel. On September 7th, 2023, tensions between police and locals erupted into violent clashes. The police opened out on the crowd with tear gas. Students were also impacted and taken to the hospital for treatment. Many groups are keeping tabs on the situation on Rempang Island, Batam. This is because locals have voiced opposition to the PSN (National Strategic Project) -designated development of the Rempang Eco City region under the administration of Joko Widodo. The nation's oligarchy and Chinese capital (PRC) are eager to grab Malay land through transactional and discriminatory policies, implementing a top-down strategy. Because of its arbitrary nature and its use of power instruments for the benefit of the oligarchy, this enterprise modelled after the VOC colonialism must be corrected, controlled by the people, and cannot be accepted.